The influence of liquidity on profitability of Polish construction sector companies - Monika Bolek; Wojciech Wili'nski (e-Finanse: Financial Internet Quarterly, 2012)
The concept of financial liquidity is not very straight, as it has various aspects, although generally it refers to the current assets and liabilities management. Financial liquidity together with profitability are the core categories of enterprise activities which, in order to function efficiently, the company should treat as equally important. The growth of financial liquidity may negatively influence the company profitability. If the company is to liquid in the static sense than it will affect negatively the profitability since some capital will be frozen in current assets. In this article, the authors analyze theoretical aspects of the relation between liquidity and profitability, whereas the empirical part they examine this interdependence on a group of construction sector companies listed on Warsaw Stock Exchange.
Keywords: G31; M21; 330; liquidity; profitability